Association between Individual Characteristics and Long COVID Severity among COVID-19 Survival in Jabodetabek - Siti Li'wuliyya; Widaad Camilah; Etis Setiawati; Hoirun Nisa (Jurnal Ilmiah Kesehatan, 2023)
Long COVID has a prevalence of between 10 and 30 percent in patients with a history of SARS-CoV-2 infection and has different levels of symptom severity. This study aimed to determine the individual characteristics based on age and sex along with the severity of Long COVID in Jabodetabek. This study used a cross-sectional design and purposive sampling technique to determine the sample size. The inclusion criteria were COVID survivors who lived in Jabodetabek and had been exposed to COVID-19 based on examination by health workers. Furthermore, the analysis carried out in this study consisted of univariate and bivariate analyses. Data collection was collected online via social media using the Post (Long) COVID-19 Syndrome Questionnaire. The Chi- square statistical test results showed that of 399 respondents, there was a statistically significant relationship between gender and the severity of Long COVID, and women were 1.6 times more at risk of experiencing more severe Long COVID-19 symptoms than men. In addition, all symptoms such as fatigue, shortness of breath, chest pain, sleep disturbances, headaches, muscle aches, anosmia, dry cough, and concentration disorders are related to the severity of long COVID. The severity level based on sex and gender in this study could be used as the basis for providing intervention and prevention of COVID-19 according to the needs of each individual's body so that the proper intervention can help reduce the severity and control of COVID-19